Chemerin in the Spotlight: Revealing Its Multifaceted Role in Acute Myocardial Infarction - Andreas Mitsis; Elina Khattab; Michael Myrianthefs; Stergios Tzikas; Nikolaos P. E. Kadoglou; Nikolaos Fragakis; Antonios Ziakas; George Kassimis (Biomedicines, 2024)
Chemerin, an adipokine known for its role in adipogenesis and inflammation, has emerged as a significant biomarker in cardiovascular diseases, including acute myocardial infarction (AMI). Recent studies have highlighted chemerin’s involvement in the pathophysiological processes of coronary artery disease (CAD), where it modulates inflammatory responses, endothelial function, and vascular remodelling. Elevated levels of chemerin have been associated with adverse cardiovascular outcomes, including increased myocardial injury, left ventricular dysfunction, and heightened inflammatory states post-AMI. This manuscript aims to provide a comprehensive review of the current understanding of chemerin’s role in AMI, detailing its molecular mechanisms, clinical implications, and potential as a biomarker for diagnosis and prognosis. Additionally, we explore the therapeutic prospects of targeting chemerin pathways to mitigate myocardial damage and improve clinical outcomes in AMI patients. By synthesizing the latest research findings, this review seeks to elucidate the multifaceted role of chemerin in AMI and its promise as a target for innovative therapeutic strategies.